The role of time pressure on the emotional Stroop task. - Sharma, Dinkar; McKenna, Frank P. (British Journal of Psychology, 2001)
Although a wide range of methodologies have been employed in examining the emotional Stroop effect, little systematic investigation of these experimental manipulations has taken place. Two experiments were designed to investigate the role of time pressure in the emotional Stroop effect. It is shown that time pressure has an important role to play in determining not only the magnitude of the effect but also whether it is possible to observe any effect at all. Reprinted by permission of the publisher.